Women in Adult Education Program for Sustainable Development: Challenges and Implications for Library and Information Services - Osuchukwu, Ngozi Perpetua; Nebolise, Ndidiamaka Lucy (Evidence Based Library and Information Practice, 2019)
Objective – Education offers advances in human and social development. It provides knowledge and resources that hold the potential for economic empowerment, resulting in a better livelihood. Hence, women need access to education with library services, if they are to have a voice, participate in sustainable development, and take care of their own health, as well as that of their children and members of their households. This paper examines the challenges women encounter in Onitsha metropolis, Anambra State, Nigeria. This study seeks to gain insight into the resources used to enhance learning, as well as the students’ perceptions and satisfaction with their learning experience.Methods – A descriptive survey research design was used. The study was carried out in five adult education centres in the city with a sample size of 120 women, randomly selected for collection of data. Questionnaire, interview, and observation methods were employed. The physical assessment of the centres was done for an evidence based report and to assess the real situations of the centres.Results – The findings show the challenges faced by Nigerian women in their pursuit of ongoing adult education included: time for the classes which are usually held in the evening, poor financial status, lack of encouragement from spouses and relations, poor learning environments, and stress. The data were analyzed using percentages and frequency counts. They are presented in tables and figures.Conclusions – It is recommended that education and library management should assess these centres for program improvements like providing more enabling environments and learning facilities. The implication of the study is that library and information services should be extended to these women to stimulate and support learning with the right attitude for active involvement in the educational activities and for enhancement of social inclusion.